2016
DOI: 10.1186/s11671-016-1373-1
|View full text |Cite
|
Sign up to set email alerts
|

Low-Frequency Self-Powered Footstep Sensor Based on ZnO Nanowires on Paper Substrate

Abstract: In this work, we design and fabricate a wireless system with the main operating device based on zinc oxide (ZnO) nanowires. The main operating device is based on piezoelectric nanogenerator (NG) achieved using ZnO nanowires grown hydrothermally on paper substrate. The fabricated NG is capable of harvesting ambient mechanical energy from various kinds of human motion, e.g., footsteps. The harvested electric output has been used to serve as a self-powered pressure sensor. Without any storage device, the signal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…In addition, there has been rapid progress on fabricating stretchable or flexible PENGs based on ZnO nanorods. The frequently used flexible substrates are sponge, 23 flexible plastic, 24 polyethylene terephthalate, [25][26][27] paper, [28][29][30] and textile fabric. 31 Among these, textile materials possess mechanical flexibility, low cost, lightweight, and used for integration into different areas such as clothing accessories.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there has been rapid progress on fabricating stretchable or flexible PENGs based on ZnO nanorods. The frequently used flexible substrates are sponge, 23 flexible plastic, 24 polyethylene terephthalate, [25][26][27] paper, [28][29][30] and textile fabric. 31 Among these, textile materials possess mechanical flexibility, low cost, lightweight, and used for integration into different areas such as clothing accessories.…”
Section: Introductionmentioning
confidence: 99%
“…[72] On the basis of the coupled piezoelectric and semiconducting properties of ZnO, the processed Kevlar fibers covered with ZnO nanowires were used to fabricate a 2D nanogenerator (NG). [74] A wind energy harvester was developed by Du et al [75] using a circular silicon plate with several symmetrically distributed rectangular cavities that were covered with ZnO thin films, and the maximum output power density was 23.39 nW cm À2 with a maximum open-circuit output voltage of 2.81 V. ZnO NGs were fabricated for low frequency (< 100 Hz) energy harvesting applications, and various NGs were developed and studied for testing under low frequency mechanical deformation.…”
Section: Znomentioning
confidence: 99%
“…Besides powering the pressure sensor, Nour et al demonstrated the feasibility of powering a wireless transmitter and LED display. [ 125 ] Furthermore, the pressure sensors only require a power supply of microwatts level, whereas the foot strike energy harvesters are capable of outputting far more energy. Therefore, Fu et al utilized an airflow energy harvester to fully power a fitness tracker consisting of a pedometer and a Bluetooth module, realizing self‐powered human activity sensing.…”
Section: Possible Self‐powered Applicationsmentioning
confidence: 99%